Development Model for the Balo' Toraja Savings and Loans Cooperative (KSP Balo'ta): Building a Core Value Based on the 'Balo'ta' Philosophy in Organizational Management - Oktavianus Pasoloran; Ade Lisa Matasik (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to build a development model for KSP Balo'ta based on the philosophy of “Balo'ta” as a guide in building core values ​​into strengths that “animate” all aspects of good co-operative governance of KSP Balo'ta. This research offers the potential to understand the philosophy of “balo'ta” which is expected to play a role in value-based communication and management. Cooperatives are organizations that have the potential and great possibility to drive social change. In facing economic difficulties, cooperatives are an option to utilize existing productive resources in the face of economic instability and efforts to improve people's welfare. The Balo'ta Savings and Loan Cooperative (KSP) is one of the pillars of the economy, especially in Toraja (Tana Toraja and North Toraja). Membership-based characteristics of KSP Balo'ta indicate that strength must be built “from the inside”. Besides that, collegiate leadership demands the same values ​​among all organizational components. One important aspect is building the basic values ​​or virtues of cooperatives (co-operative core values) as the foundation. The results of this study indicate that the process of inheritance and internalization of values ​​can be built based on history, the meaning attached to the word